Ensuring public service news provision in the era of networked communications. (June 2016) - Lowe, Gregory Ferrell; Stavitsky, Alan G
The authors argue the continuing importance of public service values for journalistic practice and news provision in the emerging context of networked communications. Divergent perspectives regarding the economic viability of news production in for-profit and nonprofit sectors are reviewed, in application to two categories of media organizations: legacy media and digital native media. The authors assess the contemporary situation for news firms in the USA and Europe to arrive at a general understanding. Results suggest the public service ethos in journalism is at risk. This encourages the importance of collaborative efforts on the part of policymakers, news providers, and the academic community to address a complex set of problems in news production and provision today. The article makes a case for preserving historic professional values in journalistic practice but is not focused on the narrower interests of a particular sector or institutional arrangement. The authors encourage developing a comprehensive contemporary news media system to secure ongoing innovation, enhance diversity, and advance quality. The article concludes with actionable proposals regarding media policy, operational partnerships, education, and professionalism.